2020
DOI: 10.3892/etm.2020.8803
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for the fetal mesencephalon to occiput measurement at 11 to 13+6�weeks of gestation

Abstract: The objective was to have a quantitative description of the normal position of the fetal midbrain in the first trimester, through defining the reference ranges for the mesencephalon to the occipital bone distance, in the axial plane. This was a prospective study that included normal fetuses screened between 11 and 13 weeks of gestation. The distance was measured between the posterior limit of the mesencephalon to the occipital bone in the same axial view as the one required for the biparietal diameter (BPD) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A study conducted in Romania between 2018 and 2019 shows that conception was spontaneous in 306 (89.5%) of the patients, and the rest had received in vitro fertilization (24 cases, 7%), or ovulation induction (11 cases, 3.2%). In total, 278 (83.5%) patients received folic acid throughout the first trimester of gestation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Romania between 2018 and 2019 shows that conception was spontaneous in 306 (89.5%) of the patients, and the rest had received in vitro fertilization (24 cases, 7%), or ovulation induction (11 cases, 3.2%). In total, 278 (83.5%) patients received folic acid throughout the first trimester of gestation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Female neonatal HC at birth in that study was lower among folic acid supplement users during the first and second trimester than in non-users. One study revealed a significant increase in foetal mesencephalon-to-occiput distance in the first trimester in women who did not receive folic acid supplementation [50]. Koning et al reported no significant association between growth trajectories of the foetal cerebellum during the first trimester of pregnancy and the time point at which supplementation was initiated with respect to conception [49].…”
Section: Folic Acid Supplement Usementioning
confidence: 99%
“…Nemescu et al (26) performed a prospective study entitled 'Reference ranges for the fetal mesencephalon to occiput measurement at 11 to 13+6 weeks of gestation' in order to obtain a quantitative description of the normal position of the fetal midbrain in the first trimester, by defining the reference ranges for the mesencephalon to the occipital bone distance, in the axial plane. This was a prospective study that included normal fetuses screened between 11 and 13 weeks of gestation.…”
mentioning
confidence: 99%